The Clean Energy Challenge - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, remarked that a key goal of the World Bank is supporting developing countries in meeting their energy demands, and helping poor people escape from poverty, and doing so with a smaller environmental footprint. It is important to build a strong partnership between rich countries and developing countries. He talked about Brazil producing ethanol on an enormous scale and with exceptional efficiency where ethanol prices have been steadily coming down in Brazilian industry, when global energy prices have been coming up. He noted the need to remove unnecessary trade obstacles that make bio fuels less competitive. He concluded by saying that the goal of World Bank’s new Investment Framework for Clean Energy and Development is to provide advice, technical assistance, and investment programs to help the partner countries meet the energy challenges while protecting the natural environment.